2004
DOI: 10.1007/s00248-003-1033-8
|View full text |Cite
|
Sign up to set email alerts
|

Plankton Diversity in the Bay of Fundy as Measured by Morphological and Molecular Methods

Abstract: Phytoplankton have traditionally been identified based on morphological characteristics. However, identifications based on morphology are time-consuming, require expertise in taxonomy, and often fail to distinguish differences among the multitudes of minute, nondescript planktonic organisms. Molecular techniques, which have revealed new insights into bacterial and picoplankton communities, may also enhance our knowledge of the diversity among communities of larger plankton. We compared plankton identifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 24 publications
5
71
1
1
Order By: Relevance
“…Recently, PCR-DGGE fingerprinting has also been applied to study the diversity and dynamics of natural plankton community [15,23]. In contrast to the morphological method, multiple samples can be analyzed simultaneously with canonical and uniform fingerprinting procedures, making it practical to perform comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PCR-DGGE fingerprinting has also been applied to study the diversity and dynamics of natural plankton community [15,23]. In contrast to the morphological method, multiple samples can be analyzed simultaneously with canonical and uniform fingerprinting procedures, making it practical to perform comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al [25] proposed that RAPD fingerprinting appeared to be more sensitive than morphological classification. With the comparison of the plankton diversity measured by the morphological method and 18S rRNA genes, Savin et al [18] suggested that molecular techniques also appeared to be better suited for revealing unidentified, but possibly ubiquitous, organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have focused on the whole eukaryotic assemblage by using eukaryote-specific primers (e.g., VAN HANNEN et al, 1998;MOON-VAN DER STAAY et al, 2000;DÍEZ et al, 2001;ESTRADA et al, 2004;SAVIN et al, 2004). However, despite the proven power of PCR-DGGE fingerprinting in microbial systems, it has not been applied with the same frequency to whole plankton communities (including bacteria and eukaryotic pelagic plankton) as it has to prokaryotes and microeukaryotes.…”
Section: Introductionmentioning
confidence: 99%